Molecular epidemiology of chicken and turkey parvovirus in Turkiye: high risk, genetic recombination signals, and first complete genome analysis - Abayli, Hasan; Aslan, Ahsen Nisa; Tonbak, Sukru; Ongor, Hasan; Akan, Mehmet (Springer Wien, 2025)
The aim of this study was to detect chicken parvovirus (ChPV) and turkey parvovirus (TuPV) on Turkish poultry farms and examine the molecular epidemiology of these viruses. In 2023, a total of 1,060 fecal samples were collected from 76 broiler farms and 30 turkey farms across various regions of Turkiye. The overall positivity rate was 72.3% (55/76) in broiler flocks and 70% (21/30) in turkey flocks. Among these, the positivity rate was 35% (7/20) in birds showing no signs of enteritis. The findings of this study suggest that, depending on the genetic variability of regional strains or the viral load, nested-PCR-based methods may prove more effective than single-step PCR for detecting ChPV and TuPV cases. Therefore, it is recommended to incorporate nested PCR in molecular epidemiological studies to minimize the risk of overlooking positive cases. Phylogenetic analysis of the VP1, VP2, and complete genome sequences of TUR/2023/ChPV and TR/2023/TuPV revealed that both strains clustered with American strains in distinct lineages. Analysis using the recombination detection programs RDP4.0 and SimPlot 3.5.1 strongly suggested that TUR/2023/ChPV may be a recombinant of strains from China and Brazil. Despite the observed genetic variability in the VP2 protein, an examination of B-cell epitopes showed a high degree of similarity between ChPV and TuPV strains. This study represents the first documentation of the emergence and prevalence of TuPVs in Turkiye, providing complete genome sequences for both ChPV and TuPV. Given the high prevalence and genetic diversity of these viruses and their presence in clinically asymptomatic birds, it is crucial for stakeholders in the poultry industry to implement regular flock screenings for these and similar viral pathogens. Proactive measures like these are essential for mitigating the economic impact of these important pathogens and developing effective preventive strategies.
Keywords: Commercial Chicken; Enteric Disease; Flocks; Prevalence; Viruses